Hakim Bukan Corong Undang-Undang, Hakim Bukan Corong Masyarakat, Dan Hakim Adalah Corong Keadilan - Ruby Falahadi; Victor Eric Fransiscus Gultom; Lucia Roida; Hendra Setiawan (Scholar Center, 2020)
Many judge has been handling the cases in court whose have not understanded the phenomenon. The judges have not consideration for methapisycal facts behind the rationality. The problems have been being the habit of our judicial process which presented the fact as evidence. So, basically from what they'd seen, heard and taken. The judges have to make decisions in case from signification behind the facts. It caused the facts in court have just raw materials. So in this case, what is the truely wish? That's the judge must be understand it. We have to admit it that so many problems finished in this country have not on the basis as the significance, resulting in it only on the area's surface. This research has used library research which emphasizes the source of information from legal books, journals, papers, newspapers, and literatures related to and relevant to the object of study. The data obtained from clarification and criticism carefully according with the reference. Using deductive analysis method, the data analysis in that weighs on rules or norms that are general and then drawn special conclusions. The practice is common in almost of indonesia judiciary. So that the expected justice is only formal and the resulting justice is based only on the facts and the formulation of the article. Therefore the judge is not a mouthpiece of the legislation or just a law enforcement as playing a puzzle unloading pairs of children's toys. The cases that befell the little people are proof that our judges are more of a punisher than a complainant. Our judges in carrying out the rule of law are very mechanistic-procedural, far from the sensitivity of justice. From these cases to be concrete evidence that Indonesian judges in examining cases or the case is always based on formal evidence, whereas formal evidence is very likely fabricated. The evidence is a case of pepper theft in Sinjai, evidence that was originally half an ounce to half a kilogram. The cases that be fell the little people are proof that our judges are more of a punisher than a complainant.